Low-Frequency Spectral Energy Distributions of Radio Pulsars Detected with the Murchison Widefield Array. (26th April 2017) - Murphy, Tara; Kaplan, David L.; Bell, Martin E.; Callingham, J. R.; Croft, Steve; Johnston, Simon; Dobie, Dougal; Zic, Andrew; Hughes, Jake; Lynch, Christene; Hancock, Paul; Hurley-Walker, Natasha; et al.
Abstract: We present low-frequency spectral energy distributions of 60 known radio pulsars observed with the Murchison Widefield Array telescope. We searched the GaLactic and Extragalactic All-sky Murchison Widefield Array survey images for 200-MHz continuum radio emission at the position of all pulsars in the Australia Telescope National Facility (ATNF) pulsar catalogue. For the 60 confirmed detections, we have measured flux densities in 20 × 8 MHz bands between 72 and 231 MHz. We compare our results to existing measurements and show that the Murchison Widefield Array flux densities are in good agreement.